The role of public university language centres in developing curiosity from the perspective of participants - احمد, د.شێرزاد علي; معروف, شێنێ خلیل (Sulaimani Journal for Humanities, 2025)
This Study aims to Find out The Role of Public Universities in Developing The Desire For Knowledge Among The Participants of Language Centers, by adopting the descriptive analytical method through the preparation of a survey form, which the researchers have prepared using the research After ensuring the accuracy of the research tool, the researchers implemented it on the research community: Language Centers (Sulaimani University, Garmian University) in 2025, which numbered (1420) participated in all four levels (Beginner, Elementary, Intermediate, Advance), the study options were (285) participants of both sexes (male, female), the most important statistical tools used consisted of G.Cooper statistical coefficient for validity of the research survey, Person correlation coefficient for stability of the research survey and percentage weight of items, the most important results of the study were: - Participants in public university language centers are strongly motivated and eager to seek information. -There is a high level of critical thinking among the participants of the language centers of public universities. - Participants in public university language centers eagerly seek information as a basis for self-learning. Finally, the researchers made some recommendations for stakeholders, as well as some suggestions for future researchers.
Keywords: Role; University; Language Centre; Development; Cognitive Curiosity